Second conference on efference on effective microorganisms (EM) - Sharifuddin, H.A.H (International nature farming research, 1993)
Contents: Effective microorganisms and their role in kyusei nature farming and sustainable agriculture, the role effective microorganisms in releasing nutrients from organic matter; the use of EM for control of root rot of strawberry.